2017
DOI: 10.1111/jace.14996
|View full text |Cite
|
Sign up to set email alerts
|

Impact of activator chemistry on permeability of alkali‐activated slags

Abstract: Durability of alkali-activated slags has been assessed by measuring the permeability using the beam-bending technique. This nondestructive technique obtains permeability values by measuring the hydrodynamic load relaxation curve of a saturated slender beam of solid paste placed in three-point bending. The impact of activator selection on the permeability of alkali-activated slags has been assessed together with the effects of water-to-precursor ratio, revealing that free silica in the activating solution is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…It has been previously shown that the percolated pore network in Portland cement paste (with w/c ratio of 0.5) is made up of pore entries-exits that are ~3nm in size, which was also found to be the case for silicate-activated slag in our previous study [4], as measured using nitrogen desorption analysis (for samples synthesized using 7 wt. % Na 2 O relative to slag, SiO 2 /Na 2 O molar ratio of 1 for the activator, and water/slag wt.…”
Section: Pore Structure Evolutionsupporting
confidence: 67%
See 3 more Smart Citations
“…It has been previously shown that the percolated pore network in Portland cement paste (with w/c ratio of 0.5) is made up of pore entries-exits that are ~3nm in size, which was also found to be the case for silicate-activated slag in our previous study [4], as measured using nitrogen desorption analysis (for samples synthesized using 7 wt. % Na 2 O relative to slag, SiO 2 /Na 2 O molar ratio of 1 for the activator, and water/slag wt.…”
Section: Pore Structure Evolutionsupporting
confidence: 67%
“…Another early-age behavior known to influence long-term performance is pore structure development. Concrete is a porous material, and the pore size controlling transport properties will dictate resistance to certain forms of degradation (often related to steel corrosion), where larger pores making up the percolated pore network lead to faster degradation rates [4].…”
Section: Early-age Behavior Of Alkali-activated Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,11 Furthermore, given correct mix designs, AAMs have comparable mechanical performance 12 and cost 7 to OPC, and can be tuned to have superior properties via specific chemical compositions, such as high thermal performance 13 and low permeability. 14 Nevertheless, questions remain regarding the long-term durability of AAMs, with the underlying degradation mechanisms often founded at the atomic/nanoscale, such as carbonation-induced chemical reactions [15][16][17][18] (from atmospheric and accelerated CO 2 conditions) and sulfate attack of the binder gel. 19,20 Progress is being made to elucidate the mechanisms responsible for chemical degradation of different types of AAMs, with the aim to pinpoint which mix designs are most resistant to different forms of degradation.…”
Section: Introductionmentioning
confidence: 99%